2021
DOI: 10.2147/cmar.s294616
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Instrumentation Failure in Titanium Mesh Reconstruction for Thoracic and Lumbar Tumors: Retrospective Analysis of 178 Patients

et al.

Abstract: Purpose To investigate risk factors for instrumentation failure (IF) in titanium (Ti) mesh reconstruction for thoracic and lumbar tumors. Patients and Methods The clinical data of patients with thoracic or lumbar tumors who received Ti mesh reconstruction via the posterior approach in our hospital from 2013 to 2018 were analyzed retrospectively. The observation indexes included sex, age, BMI, the vertebra resection mode, the number of resected vertebral segments, applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…[7][8][9][10][11][12][13] Although previous studies showed that most IFs were posterior instrument breakage, the mechanism and preceding condition had not yet been investigated in detail. [8][9][10]12,14 In our study, most IFs after TES were rod fractures preceded by CS and following kyphotic enhancement of the reconstructed level. Hence, CS is the first event in the development of IF.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…[7][8][9][10][11][12][13] Although previous studies showed that most IFs were posterior instrument breakage, the mechanism and preceding condition had not yet been investigated in detail. [8][9][10]12,14 In our study, most IFs after TES were rod fractures preceded by CS and following kyphotic enhancement of the reconstructed level. Hence, CS is the first event in the development of IF.…”
Section: Discussionmentioning
confidence: 48%
“…These reconstructions should be considered in patients with risk factors, such as lumbar level TES, multiple vertebral body resection, high BMI, and perioperative radiotherapy. [8][9][10]13,14 In addition, spinal shortening should be applied as this increases both the stability and blood flow of the spinal cord. 35,36 There are several limitations to our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bao et al. ( 40 ) found that preoperative or postoperative radiotherapy and resection of more than 2 vertebral body segments were independent risk factors for implants failure. Radiotherapy does not cause fracture of bone collagen but changes the biomechanical characteristics of the bone matrix, resulting in reduced fatigue resistance ( 41 ).…”
Section: Discussionmentioning
confidence: 99%